1994
DOI: 10.1007/bf00366869
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mechanical properties of zirconia-toughened alumina by sinter forging

Abstract: ZTA powder with a composition of 85 wt% alumina/15 wt% zirconia was prepared by a gel precipitation method. Sinter forging was performed with this powder to enhance the mechanical properties of ZTA materials. The influence of processing flaws on mechanical properties of sinter forged materials and pressureless sintered materials was investigated. Sinter forging at 40 MPa effectively decreases process flaw sizes resulting in a homogeneous microstructure and improves the grain boundary structure because of large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This Stribometer, as shown schematically in Fig. 1 (a (20-400 "C) 9.3b (20-400 "C) 7.5b (20-400 "C) 12.6 (20-100 "C) 2Sb (at 150 "C) 2.5b (at 150°C) 5.5b (at 150°C) 45.0 (at 100 "C) parallel to the steel plate. The plate is fixed by a holder, which is mounted on a heat exchanger, which in turn are supported by two steel blade springs which only allow parallel movement in the sliding direction.…”
Section: Test Equipmentmentioning
confidence: 96%
See 2 more Smart Citations
“…This Stribometer, as shown schematically in Fig. 1 (a (20-400 "C) 9.3b (20-400 "C) 7.5b (20-400 "C) 12.6 (20-100 "C) 2Sb (at 150 "C) 2.5b (at 150°C) 5.5b (at 150°C) 45.0 (at 100 "C) parallel to the steel plate. The plate is fixed by a holder, which is mounted on a heat exchanger, which in turn are supported by two steel blade springs which only allow parallel movement in the sliding direction.…”
Section: Test Equipmentmentioning
confidence: 96%
“…The densities of the sintered ceramics were measured by the Archimedes technique in mercury. The bending strength and the fracture toughness were measured by 4 point bending and single edge notched beam, respectively, as described in [5]. The Vickers hardness of ceramics were measured using a microindenter (Shimadzu Dynamic Ultra Hardness Tester DUH-200) with a maximum load of 2 N and a loading speed of 1.44 X lop3 kg s-'.…”
Section: Materials For Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconia‐toughened alumina (ZTA) ceramics have been identified for selected biomaterial applications where exceptionally high strength is required 20–22 . Strength as high as 1250 MPa and toughness as high as 9 MPa·m 1/2 have been reported for ZTAs 22–25 ; exceptional toughness and strength may be enhanced by the addition of platelet reinforcements (in the present case, crystals of β‐alumina), which encourage crack deflection. It is the terminology in the medical industry to refer to these materials as alumina matrix composites and henceforth shall be used in this paper.…”
Section: Introductionmentioning
confidence: 91%
“…17 In the case of the PECS process, Jayaseelan et al 18 reported a bending strength of 827d129 MPa for specimens containing 3 vol! ZrO 2 , and Takano et al 19 reported a linear increase in bending strength from Ĭ600 to 1620 MPa with increasing ZrO 2 content up to 50 mol!.…”
mentioning
confidence: 99%